Blind People’s Multiple Identity And Impression Management In Bandung, West Java, Indonesia - Kadri Kadri; Deddy Mulyana (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2019)
This research aims to uncover the multiple identities of 40 blind people and develop a model of their impression management that may be different from the impression management of nondisabled people. Blind people as subjects of this study are those who experience blindness in adulthood but were able-bodied before. Changes in physical conditions are followed by psychological changes that affect the way they communicate with their social environment, which is marked by impression management efforts. Using an interpretive perspective, more specifically a dramaturgical approach relying largely on observation as its method, the study reveals that the blind’s impression management is related to their self-confidence. The lower self-confidence they possess, the higher effort of impression management they make. The blind’s impression management is conducted in two strategies: first, by not using a personal front like black eyeglasses and a white stick; and secondly, by involving a performance team. These findings reinforce the distinction between the blind and the able-bodied people in their impression management. The nondisabled people usually use the personal front when managing the impression on the front stage. Based on finding that the blind’s impression management is distinctive in nature, this study has enriched Goffman's dramaturgical theory.